Resepsi Khalayak terhadap Karakter Difabel dalam Film Wonder - Revi Andrean Siregar; Hapsari Dwiningtyas Sulistyani (Interaksi Online, 2019)
The meaning of the active audience makes the text in a film has rich meaning. This is because the audience actively produces meaning based on their background, experience and daily life. Film Wonder is a film that strives to show diffable characters as individuals who have potential, just like the general public, and are treated equally by the surrounding environment. However, the Wonder film also tried to show diffable characters by using disable characteristics, such as different people, being marginalized, being objects of jokes and intimidation, and need to be pitied. However, the meaning of an active audience is not necessarily in line with the alternative ideas that media texts offer in the Wonder film. Thus, this study aims to describe the meaning of active audiences towards diffable characters in the Wonder Film. Using a qualitative-descriptive approach and reception analysis method with John Fiske's semiotic television and Stuart Hall's reception data analysis techniques. Research subjects are diffable and non-diffable audiences. The paradigm in this study uses interpretive and the theory used is the Acceptance Theory, the Representation Theory and the Stereotype Theory. The results of this study succeeded in choosing fifteen preferred reading that featured disable and diffable characters in the text offered by the Wonder film. Through the preferred reading, the results of this study indicate that there are differences in the position of the meaning of the audience towards the diffable characters in the Wonder film between non-diffable and diffable informants. Non-diffable informants have a tendency to interpret diffable characters in negotiations. This is because informants interpret diffable characters in a dilemma, where direct interaction with diffable makes informants have a tendency to approve texts that illustrate that diffable have the potential and look like society in general, however, informants' ignorance of diffable groups makes stereotypes and representations that detrimental to participating in the production process of the meaning of the informant. Meanwhile, diffable informants interpreted diffable characters in Wonder films tending to be dominant. The informant said that they were just like the general public, who have emotional and can do excellent in doing a thing very well liked. The meaning arises based on the experience of the informant who directly got achievements and did creations. In the other hand, diffable informants also tend to disagree with texts that are detrimental to groups with diffable, such as discriminating between diffable only from physical forms.